MAKNA TRADISI SEDEKAH BUMI DAN LAUT PADA RITUAL RUAT LAUT CARITA, PANDEGLANG, BANTEN - Rian, Hilda (Department of Language and Literature, Faculty of Cultural Studies, Universitas Brawijaya, 2025)
This study aims to uncover the philosophical meaning and socio-cultural values ??inherent in the Earth and Sea Alms (Ruwat Laut) tradition at Carita Beach, Pandeglang, Banten, while also examining how this tradition adapts to modernization and tourism development. Ruwat Laut is an annual ceremony for fishing communities, serving as a means of expressing gratitude for the abundance of marine resources and praying for safety. A qualitative approach with a descriptive ethnographic design and a single case study was used in this study. Data were collected through participant observation during the ritual during the month of Muharram, in-depth interviews with traditional leaders, fishing elders, and tourism practitioners, and field documentation. The research findings show that Ruwat Laut Carita is a harmonious form of cultural syncretism, combining Islamic teachings with local traditions. Its philosophical meaning includes respect for the sea as a source of livelihood, strengthening social solidarity through the practice of mutual cooperation, and instilling environmental conservation values. However, this tradition is currently at a point of tension between its sacred function maintained by fishermen and traditional leaders, and the orientation of tourism that tends towards commercialization. Despite this, Ruwat Laut continues to demonstrate its ability to adapt and thrive as a tourist attraction that supports the local economy without abandoning its core traditional values. This study recommends the need for policies that balance the conservation of sacred values ??with the development of sustainable cultural tourism.